2017
DOI: 10.1007/s00404-017-4384-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of heterotopic pregnancy following embryo transfer: clinical analysis of 55 cases from a single institution

Abstract: Routine TVS at day 27 after ET could facilitate the diagnosis of HP, symptoms onset before or after day 27 are clues to early diagnosis. Prompt surgery after diagnosis may improve the prognosis of HP following ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Because most studies reported data on small sample sizes or case reports, the most common ectopic site of HP has not been well established, but tubal EP in those with an HP is considered the most frequent site, similar to those with EP alone. [ 5 , 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Because most studies reported data on small sample sizes or case reports, the most common ectopic site of HP has not been well established, but tubal EP in those with an HP is considered the most frequent site, similar to those with EP alone. [ 5 , 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI may not always be easily accessible and the use of gadolinium contrast in HIP should be avoided in the presence of viable intrauterine pregnancy [15]. In the setting of artificial reproductive technology, only half of the heterotopic pregnancy was detected at first routine ultrasound examination [7], although higher figure of 85% has been quoted in smaller studies that proposed for routine transvaginal ultrasound at day 27 after embryo transfer [11]. In the case report, pelvic MRI was utilised to further delineate interstitial pregnancy from other potential diagnosis such as angular pregnancy or degenerating fibroid.…”
Section: Discussionmentioning
confidence: 99%
“…Serial β-hCG has roles in detecting persistent interstitial pregnancy and differentiating intrauterine pregnancy from ectopic pregnancy [11,17]. The typical doubling of serial β-hCG reading with viable intrauterine pregnancy may pose false reassurance to the clinician, resulting in missing the concomitant interstitial pregnancy in HIP [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations